2021
DOI: 10.1038/s41598-021-00672-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of pretreatment on the elemental composition of ash derived from selected Nigerian lignocellulosic biomass

Abstract: Lignocellulosic biomass is an important source of renewable energy and a potential replacement for fossil fuels. In this work, the X-ray fluorescence (XRF) method was used to analyze the elemental composition of raw and pretreated lignocellulosic biomass of cassava peels, corn cobs, rice husks, sugarcane bagasse, yam peels, and mixtures of cassava peels and yam peels, corn cobs and rice husks and all five biomass samples combined. The influence of particle size on elemental properties was investigated by scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, recycled pulp (i.e., dried once), contrasting to virgin pulp (i.e., never-dried), produces CNF films with reduced tensile strength and swelling capacity, thereby reducing recyclability [ 28 , 48 , 78 ]. Whereas mixed wastes, e.g., food and garden waste in MSW, possessing heterogenous compositions may cause high costs, requiring more flexible and complex processing in the biorefineries, compared to their homogeneous fractions deriving from forestry and agriculture [ 79 , 80 , 81 ]. In the UK ( Table 5 ), the primary waste streams (F1–F15) are likely to produce packaging films with better strength and recyclability, albeit using less processing compared to the processed and mixed wastes from flows F16–F28.…”
Section: Resultsmentioning
confidence: 99%
“…For example, recycled pulp (i.e., dried once), contrasting to virgin pulp (i.e., never-dried), produces CNF films with reduced tensile strength and swelling capacity, thereby reducing recyclability [ 28 , 48 , 78 ]. Whereas mixed wastes, e.g., food and garden waste in MSW, possessing heterogenous compositions may cause high costs, requiring more flexible and complex processing in the biorefineries, compared to their homogeneous fractions deriving from forestry and agriculture [ 79 , 80 , 81 ]. In the UK ( Table 5 ), the primary waste streams (F1–F15) are likely to produce packaging films with better strength and recyclability, albeit using less processing compared to the processed and mixed wastes from flows F16–F28.…”
Section: Resultsmentioning
confidence: 99%
“…They also have an adverse effect ( fouling, slagging, agglomeration, and corrosion) on power generation plants that use biomass for direct combustion [41]. However, research studies have shown that pretreatment of biomass cassava peels, corn cobs, rice husks, sugarcane bagasse, yam peels [44]; pine bark and switchgrass [41]; rice and wheat straw [45] reduces these elements to minimal concentration. Therefore, the low concentration of elemental compounds in Nigeria groundnut shells and cowpea shells is an added advantage, since reducing its elemental composition will require minimal pretreatment.…”
Section: Xrf Analysismentioning
confidence: 99%
“…This criterion indicates whether an LC stream comprises raw, processed, homogenous or mixed materials, determining its requirements for handling or processing operations and the resulting bioplastics quality [77]. Refined biomass is different by chemical composition and processing history than their raw counterpart, therefore results in CNF films differing by properties, processability or performance [28,29,46].…”
Section: Physical Composition (C2)mentioning
confidence: 99%